Cellulose Nanocrystals (CNCs) and Cellulose Nanofibers (CNFs) as Adsorbents of Heavy Metal Ions - Tjhang Winny Kurniawan; Hermin Sulistyarti; Barlah Rumhayati; Akhmad Sabarudin (Journal of Chemistry)
The isolation of nanocellulose has been extensively investigated due to the growing demand for sustainable green materials. Cellulose nanocrystals (CNCs) and cellulose nanofibers (CNFs), which have the same chemical composition but have different morphology, particle size, crystallinity, and other properties depending on the precursor and the synthesis method used. In comparison, CNC particles have a short rod-like shape and have smaller particle dimensions when compared to CNF particles in the form of fibers. CNC synthesis was carried out chemically (hydrolysis method), and CNF synthesis was carried out mechanically (homogenization, ball milling, and grinding), and both can be modified because they have a large surface area and are rich in hydroxyl groups. Modifications were made to increase the adsorption ability of heavy metal ions. The Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), thermogravimetric (TG), and dynamic light scattering (DLS) can reveal the characteristics and morphology of CNCs and CNFs. The success and effectiveness of the heavy metal adsorption process are influenced by a few factors. These factors include adsorbent chemical structure changes, adsorbent surface area, the availability of active sites on the adsorbent’s surface, adsorption constants, heavy metal ionic size differences, pH, temperature, adsorbent dosage, and contact time during the adsorption process. In this review, we will discuss the characteristics of CNCs and CNFs synthesized from various precursors and methods, the modification methods, and the application of CNCs and CNFs as heavy metal ion adsorbents, which includes suitable isotherm and kinetics models and the effect of pH on the selectivity of various types of heavy metal ions.